On the hunt [large type] - Johansen, Iris (Johansen, Iris. Kira Drake series, 2024)
Kira Drake has come to Paris with her highly trained Golden Retriever, Mack, to investigate the horrific bombing of a museum in the shadow of the Eiffel Tower. What she doesn't know is that one powerful man has a special reason to find the person responsible. Jack Harlan has all the money in the world, but it can't bring his brother back. His sibling was murdered during the theft of a scientific discovery that could have made the world a better place. Now, after a four-year search, Harlan learns that the Paris bombing was the work of the same twisted man. Kira and her dog are in demand by law enforcement agencies all over the world, but Harlan convinces her to continue the investigation for his own purposes, wherever it may lead on the globe. So against her better judgment, Kira finds herself on the hunt and placing her trust in Harlan--for what she hopes is justice... when what he may be seeking is vengeance--